Demokrasi Liberal dan Rekonstruksi PAI Kontemporer: Menimbang Ulang Akar Historis dan Arah Transformasi - Shyrly Mayshinta Bella; Moh. Kusno (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2026)
Liberal democracy emphasizes individual freedom, public participation, and respect for differences of opinion. In education, these values are reflected through dialogic and participatory learning. However, various studies indicate that Islamic Religious Education (IRE) is still dominated by teacher-centered approaches, resulting in limited student participation in the learning process. This condition reveals a gap between democratic values and contemporary IRE practices. This study aims to analyze the relevance of liberal democratic values in Islamic Religious Education and to formulate the direction for the reconstruction of contemporary IRE from the perspective of liberal democracy. The findings indicate that liberal democratic values, such as freedom of thought, active participation, tolerance, and respect for differences, are relevant to the principles consultation (shura), justice, and responsibility. Therefore, the reconstruction of Islamic Religious Education should be directed toward more dialogic, participatory, humanistic, and student-centered learning to address the challenges of contemporary society while maintaining the fundamental values of Islam.